Effects of erinacine A-enriched Hericium erinaceus on elderly hearing-impaired patients: A double-blind, randomized, placebo-controlled clinical trial. (October 2022) - Chan, Yin-Ching; Lin, Tzu-Chun; Chen, Chin-Chu; Lee, Li-Ya; Chen, Wan-Ping; Liu, Ya-Zue; Hwang, Juen-Haur
Graphical abstract: Highlights: Hericium erinaceus more effective for patients aged ≧ 65 than those aged < 65. Neurotrophic growth factor levels elevated by consumption of Hericium erinaceus. Pure tone audiometry was improved with Hericium erinaceus. Speech recognition was ameliorated by Hericium erinaceus. Abstract: We aimed to investigate the effects and mechanisms of Hericium erinaceus (HE) on hearing degeneration. By a double-blind, randomized, clinical trial, all 80 hearing-impaired patients aged 50–79 were randomly divided into the two groups, which received HE mycelia (2000 mg/day) and placebo boluses for eight months, respectively. A student's t -test was used to evaluate the differences of the average pure tone hearing threshold of all, low, and high frequencies (PTA-all, PTA-low, and PTA-high); speech recognition threshold (SRT); speech discrimination score (SDS); and serum concentrations of brain-derived neurotrophic factor (BDNF) and neurotrophic growth factor (NGF) between the two study groups. Subgroup analysis by age showed that PTA-high-Right, PTA-all-Left, PTA-high-Left, SRT-Right, SRT-Left, and NGF were significantly different between the two groups among patients aged ≧ 65. HE mycelia treatment could ameliorate hearing loss, especially for high frequencies and speech recognition, and increase NGF in patients aged ≧ 65.